PARK2 Suppresses Proliferation and Tumorigenicity in Non-small Cell Lung Cancer - Duan, Huijie; Lei, Zhong; Xu, Fei; Pan, Tao; Lu, Demin; Ding, Peili; Zhu, Chunpeng; Pan, Chi; Zhang, Suzhan (Frontiers in Oncology, 2019)
Aims: PARK2 mutation is originally associated with the progression of Parkinson’s disease. In recent years, PARK2 has been reported as a tumor suppressor gene in various cancers, including lung cancer. However, the biological functions and potential molecular mechanisms of PARK2 in non-small cell lung cancer (NSCLC) are still unclear. Methods: The level of PARK2 expression in 32 tissue samples of NSCLC and matched non-tumor lung tissues was detected by Western blot, and 64 specimens of NSCLC tissues were detected by immunohistochemistry. H1299 and H460 cell lines were used to PARK2 overexpression models, and H460 cell line was also used to PARK2 knockdown model. Using cell viability, colony formation, cell cycle, apoptosis, migration, and invasion assay, the biological functions of PARK2 were evaluated and the potential molecular mechanism of PARK2 was investigated in vitro. Meanwhile, 22 nude mice were employed for in vivo studies. Results: Western blot analysis revealed a decrease of PARK2 protein expression in human NSCLC samples. Immunohistochemistry also identified a vastly reduced expression of PARK2 in NSCLC (72%) and low PARK2 expression was significantly associated with tumor histological grade, lymph node metastasis and advanced TNM stage. Overexpression of PARK2 suppressed cell proliferation, colony formation, migration, and invasion, arrested cell cycle progression in the G1 phase, and induced apoptosis in human non-small cell lines H1299 and H460 in vitro. Meanwhile, knockdown of PARK2 had the opposite biological functions. In addition, PARK2 significantly decreased the tumor volumes in subcutaneous xenograft model and reduced the incidence of metastatic tumors in the transfer model. Exploration of the molecular mechanism of PARK2 in NSCLC showed that PARK2 negatively regulated the EGFR/AKT/mTOR signaling pathway. Conclusions: PARK2 was an important tumor suppressor in NSCLC, which might inhibit cancer growth and metastases through the down regulation of the EGFR/AKT/mTOR signaling pathway.